An Analysis of Annual Turnover Rates for Canadian Union Presidents - Chaison, Gary; Rose, Joseph (Relations industrielles / Industrial Relations, 1977)
This paper re-examines the common views that presidential turnover occurs infrequently, is often the result of political forces and provides an adequate measure of union democracy. Moreover, the authors try to determine to what extent environmental factors influence annual presidential turnover rates among Canadian national unions.